Pengaruh Penambahan Nanoselulosa terhadap Stabilitas Emulsi Santan sebagai Enkapsulan Kurkumin: Stabilitas Emulsi dan Kurkumin - Amaliatul Khusna; Chatarina Lilis Suryani; Thunnalin Winuprasith; Saptya Fajar Pertiwi; Erista Adisetya; Ichlasia Ainul Fitri (Jurnal Teknologi dan Industri Pangan, 2023)
Curcumin is a bioactive compound characterized by its non-polar nature and low stability. Encapsula-tion of curcumin using emulsion system such as coconut milk can increase its stability. However, emulsion systems tend to become unstable during food processing and storage. Therefore, stabilizers and emulsifiers are necessary to ensure stability. Natural stabilizers are preferred over synthetic ones. In this study, nano-celluloses, including nanocrystalline and nanofibrillated cellulose, were used as a stabilizer, and whey pro-tein isolate (WPI) was used as an emulsifier. The primary objective of this study was to investigate the impact of different types and concentrations of nanocellulose on the stability of curcumin and oil-in-water (o/w) emulsions in coconut milk. Two types of commercial nanocellulose materials were utilized: nanocrystalline cellulose (NCC) and nanofibrillated cellulose (NFC). Additionally, a combination of both NCC and NFC was used at concentrations of 0.125 and 0.25% (w/w). The results revealed that the viscosity increased as the concentration of nanocellulose increased. The particle size increased at higher concentrations of NFC and the combination of NCC and NFC, while it decreased with increasing NCC concentration. The lightness va-lue (L*) decreased with higher concentrations of nanocellulose in all sample types. However, this difference was not visually significant. In terms of curcumin stability, the addition of nanocellulose, particularly NFC at a concentration of 0.25%, led to an increase in stability. Higher viscosity resulted in an extended shelf life because it slowed down the rate of creaming index as compared to the control emulsion. Increasing the concentration of nanocellulose enhanced the effectiveness of maintaining the stability of curcumin and oil-in-water emulsions in coconut milk due to the higher viscosity. NFC as well as the combination of NFC and NCC at a concentration of 0.25% proved to be the most preferable option for achieving the highest stability.